Long-term trends and interannual variability of forest, savanna and agricultural fires in South America. Issue 6 (December 2013) - Chen, Yang; Morton, Douglas C; Jin, Yufang; Collatz, G James; Kasibhatla, Prasad S; van der Werf, Guido R; DeFries, Ruth S; Randerson, James T
Background: Landscape fires in South America have considerable impacts on ecosystems, air quality and the climate system. We examined long-term trends and interannual variability of forest, savanna and agricultural fires for the continent during 2001–2012 using multiple satellite-derived fire products.Results: The annual number of active fires in tropical forests increased significantly during 2001–2005. Several satellite-derived metrics, including fire persistence, indicated that this trend was mostly driven by deforestation. Fires between 2005 and 2012 had a small decreasing trend and large year-to-year changes that were associated with climate extremes. Fires in savannas and evergreen forests increased in parallel during drought events in 2005, 2007 and 2010, suggesting similar regional climate controls on fire behavior. Deforestation fire intensity (the number of fires per unit of deforested area) increased significantly within the Brazilian Amazon in areas with small-scale deforestation.Conclusion: Fires associated with forest degradation are becoming an increasingly important component of the fire regime and associated carbon emissions.